Effect of natural and synthetic Brassinosteroids on strawberry immune response against Colletotrichum acutatum - Furio, Ramiro Nicolás (2018)
Brassinosteroids (BRs) are steroidal essential compounds for plant growth and development. It was shown that the exogenous applications of BRs induce protection against different pathogens and can give plants tolerance/resistance to different abiotic stresses. The aim of this work was to evaluate the protective effect against the fungal pathogen Colletotrichum acutatum, the causal agent of anthracnose disease, on strawberry plants treated with 24-epibrasinolide (EP24) and a formulation based on a brassinosteroid spirostanic analogue DI-31 (BB16). Treatment with both compounds induced a defense response in strawberry plants of the cv. Pájaro against avirulent isolate (M11) of C. acutatum, being more effective at the lower concentration of both steroids (0.1 mg l−1), although the analogue BB16 showed a stronger effect than EP24. The evaluation of biochemical defense markers showed that strawberry plants treated with EP24 and BB16 increased the production of H2O2, O2.-, NO, calcium oxalate crystals and higher callose and lignin deposition as compared to the control plants. However, stomatal closure was only observed in plants treated with BB16. These results suggests that BB16 and EP24 can be used for the activation of innate immunity in strawberry plants, as a new strategy for crop health protection management, alternative to agrochemicals.